Investigations on Terminalia arjuna Fruits: Part 2- Isolation of Compound from ethyl Acetate Fraction (Bangladesh Journal of Scientific and Industrial Research, 2008)
Arjun (Terminalia arjuna) is used in traditional medicines for the treatment of various diseases (Ahmed, 2002). The phyto-chemical studies shows that the plant contains active and medicinal principles like glycosides, alkaloids, steroids, tennins etc (Ahmed, 2002). The chemical examinations of its fruits were taken up to isolate and identify active principles. For this purpose fresh fruits of Terminalia arjuna were extracted with rectified spirit. The extract was then triturated with ethyl acetate, which was then subjected to column chromatographic separation followed by PTLC. Such separation led to the isolation and purification of compound, sitosteryl-3-o-ß-Dglucoside. The structure of compound was characterized by IR, 1H-NMR and 13CNMR spectroscopic studies. Key words : Arjun, Phyto-chemical studies, Sitosteryl, Glucosidy, Chromatographic separation.DOI: 10.3329/bjsir.v43i2.974 Bangladesh J. Sci. Ind. Res. 43(2),283-290 , 2008